Physiological and biochemical responses driven by different UV-visible radiation in Osmundea pinnatifida (Hudson) Stackhouse (Rhodophyta). Issue 12 (8th October 2020) - Schneider, Geniane; Figueroa, Félix L.; Vega, Julia; Avilés, Antonio; Chaves, Patricia; Horta, Paulo Antunes; Korbee, Nathalie; Bonomi-Barufi, José
Abstract : Different radiation qualities can modulate the production of pigments and other compounds, through photoreceptors sensitive to colored lights (red, green, and blue) and UV radiation. Abstract : Light, or visible radiation, serves as a source of energy for photosynthesis of plants and most algae. In addition, light and ultraviolet radiation (UV-A and UV-B) act as a biological signal, triggering several cellular processes that are mediated by photoreceptors. The aim of this study was to evaluate the physiological and biochemical responses of Osmundea pinnatifida driven by different radiations through putative photoreceptors. For this, O . pinnatifida was grown under different radiation treatments composed by high intensity of light emitted by a low pressure sodium lamp (SOX), aiming to saturate photosynthesis, which was supplemented by low intensities of visible (red, green and blue) and ultraviolet radiation (UV-A and UV-B), in order to activate photoreceptors. Growth rates, photosynthesis, antioxidant activity, polyphenols, soluble proteins, phycobiliproteins, mycosporine-like amino acids (MAAs) and carotenoids were evaluated during the experiment. Complementary UV-A radiation positively influenced growth rates after 15 days of experiment, although the presence of a peak of blue light in this treatment can also have contributed. UV-B radiation increased the concentration of zeaxanthin and chlorophyll a . The blue light caused the accumulation of chlorophyll a, violaxanthin, phycoerythrin and polyphenols on different days of the experiment. Phycoerythrin also increased under green and red light conditions. Our results showed that some compounds can be modulated by different radiation, and the involvement of photoreceptors is suggested. In red algae, photoreceptors sensitive to red, green and blue light have been identified, however little is known about UV photoreceptors. The presence of photoreceptors sensitive to UV radiation in O. pinnatifida is discussed.